Acute Changes on Pulmonary Pressure Following Percutaneous Secundum Atrial Septal Defect Closure - Wiryanto J., et al (ACI (Acta Cardiologia Indonesiana), 2017)
Acute Changes on Pulmonary Pressure Following Percutaneous Secundum Atrial Septal Defect Closure